1976
DOI: 10.1302/0301-620x.58b4.1018029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical function as an influence on the structure and form of bone

Abstract: Rosette strain gauges were attached to the cranial and caudal aspects of the proximal half of the radius in eight skeletally mature female sheep; The sheep's radius has a slight cranially convex curvature. During walking it was deformed so that the cranial surface was subjected to tension aligned along the bone's lon axis, and the caudal surface to compression similarly aligned. The compressive strain on the caudal aspect of the bone was consistently larger (X 1-9) than the tensile strain on the cranial aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(85 citation statements)
references
References 11 publications
3
79
0
2
Order By: Relevance
“…Whereas the straight metacarpus experiences compression on the cranial, caudal and medial surfaces, reflecting overall axial compression, the radius experiences compression on its concave caudal surface, as well as its medial cortex, and tension on its convex cranial surface, reflecting bending that results primarily from axial loading about the bone's longitudinal curvature, rather than extrinsic bending loads (Fig.路2A, Figs路3, 4). These strain distributions are consistent with previous findings in which the predominant loading mode in the ungulate radius was axial compression with superimposed cranio-caudal bending (Lanyon and Baggott, 1976;Goodship et al, 1979;Lanyon et al, 1982;Rubin and Lanyon, 1982;Biewener et al, 1983a;Biewener and Taylor, 1986;Bertram and Biewener, 1988;Bertram and Biewener, 1992).…”
Section: Effect Of Bone Curvature On the Variability Of Strain Pattersupporting
confidence: 92%
See 1 more Smart Citation
“…Whereas the straight metacarpus experiences compression on the cranial, caudal and medial surfaces, reflecting overall axial compression, the radius experiences compression on its concave caudal surface, as well as its medial cortex, and tension on its convex cranial surface, reflecting bending that results primarily from axial loading about the bone's longitudinal curvature, rather than extrinsic bending loads (Fig.路2A, Figs路3, 4). These strain distributions are consistent with previous findings in which the predominant loading mode in the ungulate radius was axial compression with superimposed cranio-caudal bending (Lanyon and Baggott, 1976;Goodship et al, 1979;Lanyon et al, 1982;Rubin and Lanyon, 1982;Biewener et al, 1983a;Biewener and Taylor, 1986;Bertram and Biewener, 1988;Bertram and Biewener, 1992).…”
Section: Effect Of Bone Curvature On the Variability Of Strain Pattersupporting
confidence: 92%
“…Given the differences in variance of these parameters between outdoor and treadmill locomotion, it is interesting that the proportion of footfalls in the expected bone loading zone is nearly the same for both conditions (Fig.路5C) suggesting that the general loading pattern for the cranial and caudal surfaces of both forelimb bones is predictable, even during non-steady behaviors. This is consistent with previous studies in which surface midshaft strains recorded in the long bones of a number of species over a range of speeds and gaits showed uniform strain patterns (Lanyon and Baggott, 1976;Rubin and Lanyon, 1982;Biewener and Taylor, 1986). Additionally, the mean values for FTSR and TSO were nearly identical for the treadmill and outdoor activities.…”
Section: Bone Strain Variability During Steady Versus Non-steady Locosupporting
confidence: 91%
“…Although the proximal phalanx shares similar length and width proportions with appendicular long bones, it appears to be loaded very differently than most long bones (e.g., Biewener, 1983;Gross et al, 1992). In vivo data show that curvature in weight-bearing long bones accentuates, rather than minimizes, bone strain (Lanyon and Baggott, 1976;Rubin and Lanyon, 1982;Biewener et al, 1983;Rubin, 1984;Biewener and Taylor, 1986). Over 80% of measured strain in the femur, hum茅rus, radius, ulna, and tibia is caused by bending moments (Rubin et al, 1990).…”
Section: Mechanism Of Strain Reductionmentioning
confidence: 99%
“…compression testing specimens from cortical regions habitually loaded in compression, or tension testing specimens from cortical regions habitually loaded in tension). Mechanical testing in this context is important since: (1) in vivo surface strain measurements have shown that many long bones receive a consistent direction of bending, which in most long bones occurs during the time of peak loading of stance phase in typical gait-related activities (Biewener, 1993;Biewener and Bertram, 1993;Biewener et al, 1986;Coleman et al, 2002;Fritton and Rubin, 2001;Indrekvam et al, 1991;Lanyon and Baggott, 1976;Lanyon et al, 1979;Lieberman et al, 2003) and (2) cortical bone is substantially stiffer and stronger, has different fatigue behavior and likely has greater toughness and/or energy absorption in compression than in tension or shear (Boyce et al, 1998;Burstein et al, 1976;Carter and Hayes, 1977;Jepsen et al, 2001;Norman et al, 1996;Pattin et al, 1996;Reilly and Currey, 2000;Turner et al, 2001). Because long bones must accommodate regional strain-moderelated disparities in mechanical requirements in order to ensure the beneficial aspects of strain produced by loading (e.g.…”
Section: Introductionmentioning
confidence: 99%